PENGARUH AIR REBUSAN DAUN SIRIH TERHADAP PENURUNAN SKOR PLAK (Politeknik Kesehatan Kemenkes Bandung, 2020)
Tooth and mouth disease begins with plaque formation. Plaque control can be done mechanically or chemically. Toothbrush is the main tool in carrying out mechanical plaque control. Chemical plaque control is one of mouthwash. betel plants one of which is used as a traditional mouthwash. Betel leaf has efficacy as an effective antiseptic because of the content of attrition oil which is also called as flying oil because it is volatile. in the presence of atrisi oil, betel leaf can be widely used as an antiseptic, antibacterial, antimicrobial, antifungal, and as a deodorizer. This study aims to find out information about the effect of betel leaf decoction water on plaque score reduction. This type of research is a literature study. Retrieval of data based on sources from secondary data is data obtained through articles, journals and internet sites relating to the research conducted. The results of the literature review according to research by Siti Fatimah, et al (2017), Guntur Yudha (2015) and Glaresia Mellitania (2011), stated that the effect of betel leaf decoction water on decreasing plaque scores decreased on average, starting from the results of calculating the initial score of plaque before gargling the betel leaf cooking water and calculating the plaque score after gargling the betel leaf cooking water the results are different. The results of this study are strengthened by the content of the betel leaf and the zone of bacterial inhibition according to Sri N (2014) and Bustanussalam, et al (2015) which can inhibit the bacteria on the plaque owned by the betel leaf boiled water. Thus it can be concluded that betel leaves have anti-bacterial power that can reduce plaque formation. Key words: Effect of Betel Leaf Stew Water on Plaque Decrease